Amar en cuerpo y alma - Donadío Maggi de Gandolfi, María C. (Sapientia, 2008)
Thomas Aquinas acknowledges the compound nature of man. Not only does this apply to the body and the soul, but all of man's powers and attributes reflect these two poles in the human being. Thus, love must be approached within this framework. Throughout history fragmentary perspectives on this matter have been unable to link nature, life and spirit, on the one hand, and the spirit and the senses, on the other. More over, these connections are the basis for the relation among Anthropology, Ethics, Culture and Politics. The phrase “the lover seeks the beloved” introduces the metaphysical concept of love. Therefore, since the lover somehow becomes the beloved, life and spirit should be examined together. Finally, the quest for harmony between the spirit and the body finds its accomplishment in the phrase “love each other in body and soul”.